Detecting Groundwater Temperature Shifts of a Subsurface Urban Heat Island in SE Germany - Schweighofer, Julian; Wehrl, Michael; Baumgärtel, Sebastian; Rohn, Joachim (Water, 2021)
The subsurface beneath cities commonly shows a temperature anomaly, a so-called Subsurface Urban Heat Island (SUHI), due to anthropogenic heat input. This excess heat has multiple effects on groundwater and energy resources, such as groundwater chemistry or the efficiency of geothermal systems, which makes it necessary to investigate the temporal development of a SUHI. For this purpose, temperature profiles of 38 observation wells in the German city of Nuremberg were evaluated from 2015 to 2020 and the measured temperature changes were linked to the surface sealing. The results show that the groundwater temperatures changed between -0.02 K/a and +0.21 K/a, on average by +0.07 K/a during this period. A dependence between the temperature increase and the degree of sealing of the land surface was also observed. In areas with low surface sealing of up to 30% the warming amounts were 0.03 K/a on average, whereas in areas with high sealing of over 60% significantly higher temperature increases of 0.08 K/a on average were found. The results clearly emphasize that the subsurface urban heat island in its current state does not represent a completed process, but that more heat energy continues to enter the subsoil within the city than is the case with near-natural land surfaces.
CRIS-Team WoS Importer:2021-06-04